Penerapan Model Problem Based Learning untuk Meningkatkan Pemahaman Konsep Iman kepada Malaikat di Kelas VI SD Negeri 034 Pintu Padang Julu - Mora Indah; Dalimunthe , Siti Suriani; Mei Yuliana; Damairah; S.Hasibuan, Rosmida Sukmah; Ikhsan Muda (CV. Alfa Pustaka, 2025)
This community service aimed to improve students' understanding of the concept of faith in angels through the implementation of Problem Based Learning (PBL) model in grade VI of SD Negeri 034 Pintu Padang Julu. The implementation involved 28 students and utilized PBL approach with authentic problems related to faith in angels in daily life context. Pre-test and post-test methods were employed to measure students' understanding improvement, complemented by observation and interviews with teachers and students. Results showed significant improvement in students' understanding of the concept of faith in angels, with average scores increasing from 68.5 to 85.2. Students demonstrated better comprehension of angel characteristics, their duties, and the significance of believing in angels in Islamic faith. The PBL model proved effective in developing critical thinking skills and connecting abstract concepts with real-life situations. Teachers reported positive responses regarding the implementation of this student-centered learning approach. Success factors included appropriate problem design, active student collaboration, and strong pedagogical support from teachers. The program also produced learning modules and teacher guidelines for sustainable implementation.